Intensification of innovation processes on the basis of economy clustering - Lavrukhina, K.; Kushik-Strelnikov, J.; Novikov, D. (Ways to Improve Construction Efficiency, 2018)
The problems of innovative processes intensification are considered, operational innovative infrastructure is analyzed, new infrastructure elements are examined, namely clusters, which ensure interconnection and mutual augmentability of industrial sectors, their advantages and necessity of further development are explored with the view of innovative processes intensification in the region.